Sustainability considerations and willingness to try alternative proteins: evidence from the UK - Albert Boaitey; Beth Clark; Pattanapong Tiwasing (Cleaner and Responsible Consumption)
Reductions in the consumption of livestock products in Western diets are considered necessary to mitigate some of animal productions' impacts on human health, animal welfare and the environment. Whilst several alternative protein products are on the market or being developed, the motivations for consumer decision-making are not well-understood. In particular, given the focus on improved sustainability as justification for these alternative proteins, understanding the relationship between sustainability considerations and willingness to try (WTT) remains important. This study uses data from 1929 UK individuals to evaluate the potential role of sustainability considerations (health, animal welfare, environmental, financial) on WTT three alternative protein products: plant-based, cultured meat, and edible insects. Ordered probit and quantile regression models are used to explore WTT, with controls for respondents' sociodemographic characteristics and level of awareness. The findings show that sustainability considerations particularly ethical and environmental concerns remain relevant in the WTT alternative proteins in the UK. Their potential role however varies across products and consumer segments. There is also significant variation in WTT due to factors related to familiarity with specific alternative protein types and respondent's socio-demographic characteristics (i.e., gender, education, age, marital status, household size, number of children and household income). Recommendations are made for strategies to promote the alternative protein products examined based on these findings.